Development of Physical Education Learning Media for Basketball Material Based on Android-BASUKA - Fikri Hidayat; Ibnu Fatkhu Royana; Galih Dwi Pradipta (Musamus Journal of Physical Education and Sport (MJPES), 2024)
Objective. This study aims to develop Android-based basic basketball technique learning media at SMAN 1 Mlonggo Jepara. This study is expected to provide benefits both theoretically and practically. Materials and Methods. The method used in this study is development research. The development procedures used are potential and problem analysis, collecting information, product design, product validation, product revision, and product trials. Data collection techniques used are interviews and questionnaires. Results. The product validation data from material experts in stage I obtained an average score of 3.9 or a good category and in stage 2 obtained an average score of 4.1 or a very good category. While the media expert in stage I obtained a score of 4.25 very good and in stage II obtained a score of 4.55 or a very good category. In the small-scale test, the appearance aspect obtained an average score of 4.1 or a very good category and in the content aspect obtained an average score of 4.0 or a good category. In the learning aspect, an average score of 4.0 or a good category was obtained. Meanwhile, in the large-scale test, the display aspect obtained a score of 4.0 very good and the content aspect obtained a score of 4.0 or a very good category. In the learning aspect, it obtained a score of 4.1 or a very good category. Conclusion. Based on the results of the study, it can be concluded that the android-based basketball learning media named "Basuka" is said to be suitable for use as a learning medium.